Neuroplasticity in an Adolescent with Corpus Callosum Agenesis Associated with Epilepsy - Dámaris González Vidal; Osvaldo Ramón Aguilera Pacheco; Margarita Isabel Chávez Isla (Universidad de las Ciencias Médicas de Cienfuegos, 2021)
Neural plasticity represents the brain's ability to recover and restructure itself, allowing it to recover from disorders or injuries and reduce the effects of structural alterations, whether congenital or acquired. The agenesis of the corpus callosum is a malformation of the central nervous system that occurs due to lack of development or crossing of axons from the cerebral cortex, which can be associated with other malformations or be the product of destructive lesions with atrophy. From a clinical point of view, neurological disorders such as psychomotor retardation, learning, motor, visual-spatial disorders and seizures are frequent. The case of a male patient, who began with epilepsy at 17 years of age, with a magnetic resonance imaging finding of total agenesis of the corpus callosum and pachygyria, with normal psychomotor and cognitive development and favorable clinical evolution. Neuroplasticity as an adaptive physiological mechanism allowed the establishment of interhemispheric communication alternatives and consequently little flowery clinical manifestations and a good evolution of epilepsy, maintaining a normal neurocognitive state is presented. The objective of this research is to describe the unusual clinical form of agenesis of the corpus callosum associated with epilepsy and the participation of the neuronal plasticity mechanism in this oligosymptomatic form, in an adolescent.